2007
DOI: 10.1002/eji.200737408
|View full text |Cite
|
Sign up to set email alerts
|

Donor double‐negative Treg promote allogeneic mixed chimerism and tolerance

Abstract: Bone marrow (BM) transplantation is an efficient approach to develop donor-specific tolerance and prevent chronic rejection. Allogeneic BM transplantation is limited by donor T cell-mediated graft-versus-host disease, requirement of cytoreduction and high numbers of BM cells. In addition of these drawbacks, recent studies demonstrate that not only T cells, but also NK cells can mediate BM rejection, and long-term mixed chimerism depends on NK cell tolerance. Thus, NK cell is another potential barrier against e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 70 publications
(104 reference statements)
2
29
0
Order By: Relevance
“…Subsequent studies reported that DN Tregs displayed antigen specific suppressive activity both in vitro and in vivo (51). DN Tregs not only suppress CD8+ T cell responses, but also inhibit CD4+ T cells (57), B cells (58), NK cells (59), and dendritic cells (DC) (60). …”
Section: Tcrαβ+ Cd4-cd8- Double Negative Tregs (Dn Treg)mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies reported that DN Tregs displayed antigen specific suppressive activity both in vitro and in vivo (51). DN Tregs not only suppress CD8+ T cell responses, but also inhibit CD4+ T cells (57), B cells (58), NK cells (59), and dendritic cells (DC) (60). …”
Section: Tcrαβ+ Cd4-cd8- Double Negative Tregs (Dn Treg)mentioning
confidence: 99%
“…As might be expected, anti-donor IgM and IgG antibody titers were significantly diminished in recipients of adoptively transferred DN Tregs (58). In a model of murine allogenic bone marrow transfer, DN Tregs supported graft survival through suppressing NK cells by perforin and Fas-FasL dependent pathways (59). …”
Section: Tcrαβ+ Cd4-cd8- Double Negative Tregs (Dn Treg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, TCR transgenic and non-transgenic DN T cells can also inhibit NK cells (He et al, 2007; Su et al, 2012), B cells (Zhang et al, 2006; Hillhouse et al, 2010; Ford McIntyre et al, 2011), and dendritic cells (Gao et al, 2011). The combination of their distinct phenotypic characteristics and their unique antigen-specific immunoregulatory properties toward multiple cellular targets has prompted investigators to examine the role of DN T cells in various disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, regulatory DN T cells have been shown to promote allograft and xenograft tolerance (12)(13)(14)(15)(16)(17), limit the incidence of graft versus host disease (17)(18)(19)(20), as well as provide resistance to autoimmune diabetes development in different animal models (21)(22)(23). Specifically, autoimmune-prone mice carry fewer DN T cells, and injection of DN T cells has been shown to be sufficient to reduce the incidence of autoimmune diabetes in two distinct TCR transgenic mouse models (21,22).…”
mentioning
confidence: 99%